Glideapp Based E-module Learning Media Innovation as a Support For Student Practicum in Basic Boga Courses - Agustina, Dian; Mutiara, Erli; Ginting, Laurena; Anugerah, Ajeng Inggit (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Technology affects the progress of education, where its development has an impact on the learning process including in higher education. Showing the idea or introduction of new things renewal of new discoveries that are different from existing or previously known. one of them is about the existence of electronic-based media used in the learning process. Electronic-based modules or e-modules become media by utilizing technology. Glideapps-based e-modules are an alternative in learning without print media. By innovating teaching media from manual to electronic-based learning resources, this study was conducted to determine the feasibility of e-modules as an alternative teaching material that can support the learning process by utilizing technological advances, because it contains material, images, and videos so that students can easily understand the material. In practice, students are given the freedom to access various things related to learning, including activities in class or laboratory practicum in basic culinary learning. This is the basis that it is very necessary by utilizing this technology to facilitate the course of learning, with glideapps-based e-modules as teaching materials to support practicum in basic food courses. This type of research is a type of development research conducted using the 4-D development model (Define, Design, Develop, and Disseminate). It is known that the results of research on the development of glideapps-based e-module media by obtaining media feasibility from material expert validation got a percentage of 85.80% with a very feasible category, then media expert validation got a percentage of 80.65% with a feasible category, and student responses got a percentage of 93.03% with a very feasible category. Based on the results obtained from this study, it is concluded that the glideapps-based e-module is feasible to use. Keywords: Technology, E-Module, Glideapps, Basic Boga, 4D